Implementation of Drinking Water Supply Programs And Sanitation Community Based (PAMSIMAS) (at Blora District, Blora Regency, Central Java) - Noor, Munawar; Diah, Christine; Tedjo, Pratiwi (Advances in Social Sciences Research Journal, 2020)
This research was initiated from the Pamsimas program targets have not yet been achieved. The causes were limited water sources and raw water supply, sanitation and hygiene behavior, public awareness of the importance of healthy living behavior was low. This study was to describe and analyze the implementation of the Pamsimas program and the supporting/inhibiting factors of the Program. This study used a qualitative approach by selecting key-informants based on a purposive sample technique. The results showed that the the implementation of the Pamsimas Program in Blora Sub-district was not optimal in terms of the variables as a prerequisite for program implementation. These prerequisites tend to be rigid, making it difficult for program implementers in the field to make decisions that are not included in the standard operational procedures (SOP). On the other hand, the individual and community behavior and participatory to the program in supporting the provision of clean water to be positiveBesides that the factors of limited water sources and raw water supply, unsafe sanitation and drinking water remained unsolved. Recommendations of the conclusions of the study are the delegation of authority related to the bureaucratic structure, especially the standard operating procedures (SOP) and the absence / scarcity of raw water sources for clean watethat needs attention to program managers in the field.